Human Endometrial Organoids: Recent Research Progress and Potential Applications - Lou, Liqun; Kong, Shuangbo; Sun, Yunyan; Zhang, Zhenbo; Wang, Haibin (Frontiers in Cell and Developmental Biology, 2022)
Abstract Since traditional two-dimensional (2D) cell culture cannot meet the demand of simulating physiological conditions in vivo, three-dimensional (3D) culture systems have been developed. To date, most of these systems have been applied for the culture of gastrointestinal and neural tissue. As for the female reproductive system, the culture of endometrial and oviductal tissues in Matrigel has also been performed, but there are still some problems that remain unsolved. This review highlights recent developments regarding endometrial organoids, focusing on the determinants influencing endometrial glandular organization, the coculture of the gland and stroma, the individual drug screening for organoids from patients and provides a better understanding of the genome editing of endometrial organoids.